Constructing criteria for evaluating the Arabic language teacher's guide for the third intermediate grade - Waleed Sabet shreib/ Salam Naji Ghadban ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The current research aims to build criteria for evaluating the guide of the Arabic language for the third intermediate grade, and to achieve this goal the researcher adopted the descriptive method for his research. The research tool consisted of a questionnaire of 65 standard items distributed in five fields(objectives, content, methods of teaching, activities and training, form and artistic output). The researcher chose a sample of experts and arbitrators in the field of Arabic language teaching methods and the field of general curricula and teaching methods in the universities of Maysan, Basra, Babil, Wasit, and Mosul. To identify the validity of the standard paragraphs for evaluating the guide , the chi-square law (K2) was adopted, and the percentage of validity coefficient was extracted, and 80% was determined as a criterion for accepting the paragraph.